Variation in Coral Thermotolerance Across a Pollution Gradient Erodes as Coral Symbionts Shift to More Heat-Tolerant Genera - Naugle, Melissa S.; Oliver, Thomas A.; Barshis, Daniel J.; Gates, Ruth D.; Logan, Cheryl A. (Frontiers in Marine Science, 2021)
Phenotypic plasticity is one mechanism whereby species may cope with stressful environmental changes associated with climate change. Reef building corals present a good model for studying phenotypic plasticity because they have experienced rapid climate-driven declines in recent decades (within a single generation of many corals), often with differential survival among individuals during heat stress. Underlying differences in thermotolerance may be driven by differences in baseline levels of environmental stress, including pollution stress. To examine this possibility, acute heat stress experiments were conducted on Acropora hyacinthus from 10 sites around Tutuila, American Samoa with differing nutrient pollution impact. A threshold-based heat stress assay was conducted in 2014 and a ramp-hold based assay was conducted in 2019. Bleaching responses were measured by assessing color paling. Endosymbiont community composition was assessed at each site using quantitative PCR. RNA sequencing was used to compare differences in coral gene expression patterns prior to and during heat stress in 2019. In 2014, thermotolerance varied among sites, with polluted sites holding more thermotolerant corals. These differences in thermotolerance correlated with differences in symbiont communities, with higher proportions of heat-tolerant Durusdinium found in more polluted sites. By 2019, thermotolerance varied less among sites, with no clear trend by pollution level. This coincided with a shift toward Durusdinium across all sites, reducing symbiont community differences seen in 2014. While pollution and symbiont community no longer could explain variation in thermotolerance by 2019, gene expression patterns at baseline levels could be used to predict thermotolerance thresholds. These patterns suggest that the mechanisms underlying thermotolerance shifted between 2014 and 2019, though it is possible trends may have also been affected by methodological differences between heat stress assays. This study documents a shift in symbiont community over time and captures potential implications of that shift, including how it affects variation in thermotolerance among neighboring reefs. This work also highlights how gene expression patterns could help identify heat-tolerant corals in a future where most corals are dominated by Durusdinium and symbiont-driven thermotolerance has reached an upper limit.